Substance use patterns and health profiles among US adults who use opioids, methamphetamine, or both, 2015-2018. (1st September 2020) - Shearer, Riley D.; Howell, Benjamin A.; Bart, Gavin; Winkelman, Tyler N.A.
Highlights: Methamphetamine use was associated with lower income, rurality, and unstable housing. Use of both opioids and methamphetamine was associated with more chronic conditions. Use of both substances together was associated with more injection needle use. Use of both substances together was associated with more severe mental illness. Abstract: Background: Methamphetamine use, with and without opioids, has increased substantially, but little is known about the sociodemographic characteristics, substance use patterns, or health profiles of individuals who use methamphetamine. To design effective public health interventions, health care professionals and policymakers need data describing individuals who are using methamphetamine in the midst of the opioid crisis. Methods: We used 2015–2018 data from the National Survey on Drug Use and Health and included non-elderly adults aged 18–64 years. We categorized respondents into three groups: use of opioids without methamphetamine use, use of methamphetamine without opioid use, or use of both opioids and methamphetamine. Multiple logistic regression models controlling for sociodemographic factors were used to compare substance use characteristics and measures of individual health between the three groups. Results: People who used any methamphetamine were more likely to be unstably housed, low-income, and live in rural areas. Use of both opioids and methamphetamine was associated with a 132 % higher prevalence of injection needle use, and a nearly twofold higher prevalence of viral hepatitis compared with opioid use alone. One third of individuals reporting use of both opioids and methamphetamine had a severe mental illness, a 55 % higher prevalence than those using opioids alone. Conclusions: Individuals who used opioids and methamphetamine had more complex substance use and health profiles than individuals who used opioids alone. These findings suggest public health and harm reduction approaches designed to address opioid use remain important in an era of rising methamphetamine use.